STUDI BIBLIKA TENTANG KERAJAAN ALAH DI BUMI - Gidion, Gidion (Shift Key : Jurnal Teologi dan Pelayanan, 2017)
Understanding the Old Testimony and New Testimony texts about the Kingdom of God is not easy. It has many disputation regarding this topic. Eldon Ladd said that â€œThere is no teaching in the New Testimony which is debated in so much energy as this Kingdom of God topicâ€. Therefore, it can be said that the Kingdom of God topic is something which always attractive to be investigated and observed. Because the research purpose is to analyze the qualitative data in terms of literature review, the research method of this research is qualitative method with the research type of biblical study